(untitled) (International Journal of Food and Nutritional Sciences, 2022)
As new media has emerged and has become an evident part of the daily media consumption, journalism is no more restricted to news collection. A new type of journalism is emerging and its distinguishing features include ubiquitous news, accessibility to global information, instant reporting, interaction, multimedia content, and extreme content customization. This represents a potentially superior kind of journalism in many ways since it can win back a disenchanted and distrusting audience. It simultaneously poses numerous risks to the most valued principles and values in journalism. In a medium where anyone with a computer and a modem can become a global publisher, the authenticity of the content, source verification, accuracy, and veracity are all doubtful. The following study focuses on how the new media with its interactive features affects the consumption and future of news.